2018
DOI: 10.1056/nejmoa1613108
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Zika Virus in Body Fluids — Final Report

Abstract: BACKGROUND To estimate the frequency and duration of detectable Zika virus (ZIKV) RNA in human body fluids, we prospectively assessed a cohort of newly infected participants in Puerto Rico. METHODS We evaluated samples obtained from 150 participants (including 55 men) in whom ZIKV RNA was detected on reverse-transcriptase–polymerase-chain-reaction (RT-PCR) assay in urine or blood in an enhanced arboviral clinical surveillance site. We collected serum, urine, saliva, semen, and vaginal secretions weekly for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
395
7
22

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(439 citation statements)
references
References 52 publications
15
395
7
22
Order By: Relevance
“…Urine collection is also easy and non-invasive, and studies reported that ZIKV RNA can be detected more frequently in urine than in blood during the acute phase [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Urine collection is also easy and non-invasive, and studies reported that ZIKV RNA can be detected more frequently in urine than in blood during the acute phase [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the contribution of the sexual route to disease transmission may be difficult to predict in areas where ZIKV is endemic, it certainly complicates virus epidemiology in regions of nonendemicity where the mosquito vector is absent. A recent cohort study reported that 56% of males positive for ZIKV in serum were also positive for the virus in semen, and the median time until the loss of ZIKV RNA in semen was 34 days, compared to 14 days in serum, thus suggesting a much longer infectious phase of ZIKV than of other flaviviruses traditionally transmitted via mosquitoes (6). Considering the lack of any measures approved to clear ZIKV infection and the detection of RNA of other reemerging pathogens such as Ebola virus in semen (4,7), it has become critical to understand the mechanisms associated with testicular infection by ZIKV.…”
mentioning
confidence: 99%
“…In contrast, a recent study carried out in Latin America including 150 individuals with Zika virus infection reported that the mean period until the disappearance of the virus was longer in serum (14 days) than in urine (9 days). 45 This contrasting result may be affected by the presence of the five pregnant women in the participant population; the Zika virus has been shown to be detected in serum for longer periods of time during pregnancy. 46 Positive antibody test results are defined as an increase of fourfold of antibody titer in paired sera.…”
Section: Laboratory Tests and Diagnosismentioning
confidence: 99%